Enhancing Ethyl Acetate Conversion from Acetic Acid Esterification by Optimizing Reactant Mole Ratio and Reaction Temperature - Fadhila Kusriana Azizi; Mustika Sukma Arumi; Pangeran Hidayat; Raihan Dwiki Nurahman; Stela Nathalie Anggawijaya (Journal of Chemical Engineering Research Progress, 2026)
Ethyl acetate is among the most widely utilized and produced compounds in the chemical industry, serving as a key solvent in coatings, adhesives, pharmaceuticals, and various synthesis processes. Its production typically occurs through the esterification of acetic acid with ethanol, a reaction that is both exothermic and reversible. These characteristics make the control of operating conditions critically important for achieving high conversion rates and minimizing energy consumption. In this study, the optimization of two primary operating parameters, reactant ratio and temperature, was undertaken to enhance the conversion of ethyl acetate. Simulation results revealed that the optimal conditions were achieved with a reactant mole ratio of 3:1 at a temperature of 135.7 °C, resulting in an ethyl acetate conversion of 97.21%. These findings underscore the significance of systematic parameter optimization in improving process efficiency, reducing costs, and supporting sustainable production practices within the chemical industry. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).